2015
DOI: 10.1097/pgp.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Role of Apoptosis in the Development of Uterine Leiomyoma

Abstract: To describe gene expression patterns of the apoptotic regulatory genes Bcl and Bax in human uterine leiomyoma tissue. To investigate the relationship between alterations of gene expression patterns and several relevant clinical parameters. We obtained samples from 101 cases undergoing surgery for uterine leiomyoma for gene expression analysis of the Bcl-2 and Bax genes. Gene expression was quantified using RT-PCR technique. In the leiomyoma group, the Bcl-2 gene was significantly overexpressed compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…On the other hand, the overexpression of Bax results in accelerated programmed cell death. According to previous studies, the anti-apoptotic mechanism seems to be involved in the development of uterine leiomyoma; several studies have demonstrated that the anti-apoptotic Bcl-2 gene was significantly over-expressed in uterine leiomyoma compared to homologous myometrium [40], and can even be influenced by the endocrine environment [41]. A previous study demonstrated that the inhibition of anti-apoptotic proteins Bcl-2/Bcl-xL promoted apoptotic cell death [42].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the overexpression of Bax results in accelerated programmed cell death. According to previous studies, the anti-apoptotic mechanism seems to be involved in the development of uterine leiomyoma; several studies have demonstrated that the anti-apoptotic Bcl-2 gene was significantly over-expressed in uterine leiomyoma compared to homologous myometrium [40], and can even be influenced by the endocrine environment [41]. A previous study demonstrated that the inhibition of anti-apoptotic proteins Bcl-2/Bcl-xL promoted apoptotic cell death [42].…”
Section: Discussionmentioning
confidence: 99%